Metabolic engineering of Bacillus amyloliquefaciens for poly‐gamma‐glutamic acid (γ‐PGA) overproduction. Issue 5 (1st July 2014) - Feng, Jun; Gu, Yanyan; Sun, Yang; Han, Lifang; Yang, Chao; Zhang, Wei; Cao, Mingfeng; Song, Cunjiang; Gao, Weixia; Wang, Shufang
Summary We constructed a metabolically engineered glutamate‐independent Bacillus amyloliquefaciens strain with considerable γ‐PGA production. It was carried out by double‐deletion of the cwlO gene and epsA‐O cluster, as well as insertion of the vgb gene in the bacteria chromosome. The final generated strain NK‐PV elicited the highest production of γ‐PGA (5.12 g l−1), which was 63.2% higher than that of the wild‐type NK‐1 strain (3.14 g l−1). The γ‐PGA purity also improved in the NK‐PV strain of 80.4% compared with 76.8% for the control. Experiments on bacterial biofilm formation experiment showed that NK‐1 and NK‐c (ΔcwlO) strains can form biofilm; the epsA‐O deletion NK‐7 and NK‐PV strains could only form an incomplete biofilm.